Haikyu!! 35, Birdcage - Furudate, Haruichi, 1983- (Shonen Jump manga., 2019)
Ever since he saw the legendary player known as “the Little Giant” compete at the national volleyball finals, Shoyo Hinata has been aiming to be the best volleyball player ever! Who says you need to be tall to play volleyball when you can jump higher than anyone else? Day 3 of the Spring Tournament gets off to a calamitous start when Karasuno makes a critical mistake and loses the first set to Nekoma! In the second set, Karasuno tenaciously attacks while Nekoma pushes through the long and grueling rallies. Karasuno manages to build a slight lead, but Kenma<U+2019>s plan slowly takes effect, and Hinata finds that he<U+2019>s constantly out of position to attack.